The Minkowski approach for choosing the distance metric in geographically weighted regression. Issue 2 (1st February 2016) - Lu, Binbin; Charlton, Martin; Brunsdon, Chris; Harris, Paul
ABSTRACT: In this study, the geographically weighted regression (GWR) model is adapted to benefit from a broad range of distance metrics, where it is demonstrated that a well-chosen distance metric can improve model performance. How to choose or define such a distance metric is key, and in this respect, a 'Minkowski approach' is proposed that enables the selection of an optimum distance metric for a given GWR model. This approach is evaluated within a simulation experiment consisting of three scenarios. The results are twofold: (1) a well-chosen distance metric can significantly improve the predictive accuracy of a GWR model; and (2) the approach allows a good approximation of the underlying 'optimal distance metric', which is considered useful when the 'true' distance metric is unknown.